Monolithic Photonic Integrated Circuit Based on Silicon Nitride and Lithium Niobate on Insulator Hybrid Platform. Issue 10 (7th July 2022) - Jiang, Yongheng; Han, Xu; Huang, Haijin; Zhang, Pu; Dubey, Aditya; Xiao, Huifu; Yuan, Mingrui; Frigg, Andreas; Nguyen, Thach Giang; Boes, Andreas; Li, Yingtao; Ren, Guanghui; et al.
Abstract : Lithium niobate on insulator (LNOI) has been demonstrated as a promising platform for photonic integrated circuits (PICs), thanks to its excellent properties such as strong electro‐optic effect, low material loss, and wide transparency window. Herein, a monolithic PIC for high‐speed data communication application on a lithium‐niobate‐etchless platform with silicon nitride (Si3 N4 ) as a loading material is proposed and demonstrated. The fabricated PIC consists of four racetrack resonator modulators and a pair of four‐channel mode (de)multiplexers, which shows high data modulation rate of 70 Gbps for single channel and the total data throughput reaches up to 280 Gbps. To the best of knowledge, this is the first demonstration of PIC consisting of high‐speed electro‐optical modulators and (de)multiplexers with such high data capacity on Si3 N4 ‐LNOI hybrid platform, which opens up new avenues for achieving large‐scale monolithic integration on LNOI platform in future. Abstract : Herein, the authors propose and demonstrate a monolithic photonic integrated circuit for high‐speed data communication based on silicon nitride and lithium niobate on an insulator hybrid platform. By combing the modulators with the four‐channel mode (de)multiplexers (MMUXs), the application for on‐chip high‐speed data communication with the 280 Gbps total data throughput has been verified.